Impact of different isothermal aging conditions on the IMC layer growth and shear strength of MWCNT-reinforced Sn-5Sb solder composites on Cu substrate - T. Temitope, Dele Afolabi; Mohamed Ariff, Azmah Hanim; O. J., Ojo Kupoluyi; R., Calin (Elsevier BV, 2019)
In this study, the effect of multi-walled carbon nanotubes (MWCNTs) reinforcement on the intermetallic compound (IMC) layer growth and shear strength of Sne5Sb-xCNT/Cu composite solder joints subjected to different isothermal aging conditions has been investigated. A series of plain and composite lead-free solder systems (Sne5Sb-xCNT; x ¼ 0, 0.01, 0.05 and 0.1 wt%) was successfully developed through the powder metallurgy method. Isothermal aging process was performed on the solder/Cu joints at 120 _C, 150 _C and 170_C temperatures in order to investigate the evolution of the interfacial IMC layers and the shear strength property. Experimental results showed that the thickness of the total IMC layer increased with rising aging temperature. While the Cu3Sn IMC maintained a layer-type morphology for all aging conditions, morphology of the Cu6Sn5 IMC transformed from a scallop-type to a layer-type after aging at intermediate (150 _C) and high (170 _C) temperatures. Given the potential of MWCNTs as a reinforcement material, significant suppression in IMC layer growth was demonstrated by the composite solder joints relative to the plain counterpart. Comprehensive investigation on the growth kinetics showed that the presence of MWCNTs in the composite solder joints was effective in slowing down the diffusion mechanism responsible for IMC growth. Overall, the Sne5Sb-0.05CNT composite solder joint exhibited the lowest diffusion coefficient within the range of 0.09 _ 10_14- 1.03 _ 10_14 cm2/s and 0.95 _ 10_14- 9.8 _ 10_14 cm2/s for Cu6Sn5 and Cu3Sn IMC layers respectively. Moreover, the strengthening effect of the MWCNTs reinforcement was well marked in the composite solder joints as the maximum shear strength within a range of 24.2e15.2 MPa was exhibited by the Sn-0.01CNT/Cu composite solder joint subjected to reflow soldering and isothermal aging conditions